Penguatan Tata Kelola Badan Usaha Milik Desa (BUMDes) Berbasis Kampung Hijau - Febrina, Rury; Marta, Auradian; Muhammad Amin, Raja; Hadi, Sofyan; Ferlan, Margina; Essio Mento, Meris (Abdimas Indonesian Journal, 2025)
Siak District encourages efforts to support sustainable development through Regional Regulation No. 4 of 2022 concerning Siak Green District. Siak Hijau District regulates the sustainable management of natural resources in several utilization zones with the aim of harmonizing efforts to save and protect the environment with the economic benefits of natural resource management, which still considers aspects of environmental sustainability. This policy goal is very strategically integrated with ecological-based BUMKam management. This community service was carried out in Dosan Village, Pusako District. The method is done through presentations, discussions, brainstorming, simulations, effective facilitation of the community and BUMKam managers to identify business opportunities that are in accordance with the natural resource utilization zone, so that it is expected to become a village development model that supports sustainable development in Siak District. The results of the service show that BUMKam Kampung Dosan can be developed through optimizing local potential. Kampung Dosan Pusako Sub-district has tourism potential in the form of Lake Naga Sakti and Khalifah Sulaiman Green Park as an effort to develop the type of BUMKam business. In addition, it is necessary to have the ability to obtain business opportunities through the establishment and management of a Waste Bank as well as clean water and environmental management by BUMKam Kampung Dosan.